If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7 = x + -27 Reorder the terms: 7 + 3x = x + -27 Reorder the terms: 7 + 3x = -27 + x Solving 7 + 3x = -27 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7 + 3x + -1x = -27 + x + -1x Combine like terms: 3x + -1x = 2x 7 + 2x = -27 + x + -1x Combine like terms: x + -1x = 0 7 + 2x = -27 + 0 7 + 2x = -27 Add '-7' to each side of the equation. 7 + -7 + 2x = -27 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = -27 + -7 2x = -27 + -7 Combine like terms: -27 + -7 = -34 2x = -34 Divide each side by '2'. x = -17 Simplifying x = -17
| 2(4c+3)=12x-6 | | f(x) = 11 x+ 2 | | 6+13=18 | | 4(x-2)-3x=2(x-4)-x | | -5x=33 | | 4y=12x+8 | | -15-45+4=59-11 | | -1.5n=18 | | 12(2w-30)=6w | | 24+x=64 | | 49p*p+6=87 | | 5x-6-2x+7=10 | | 7e-3=47 | | 4x-2x+x=15 | | .25-6=2 | | -10+x+4=-10+x+x | | 3a-b-5c=7 | | 21a+13y= | | x(5x-2)+x(2x-6)=(7x+9)(x-2) | | Y=8x-59 | | 12x^3-9x^2-40x+30= | | 8x+4+2x= | | -3s=-2.4 | | 2j+8= | | 15x+3+10x+2=180 | | .30x=22-x | | -8k+25=-3k-7(1+3k) | | v+913=-23 | | 2=3(1-4x) | | (-11)(-11)(-11)= | | .13x+.6(x-3)=.01(3x-5) | | 9(2z+3)-11=6z+100 |